Superhalogen Passivation for Efficient and Stable Perovskite Solar Cells. Issue 7 (30th April 2022) - Kim, Hobeom; Lim, Jaekeun; Sohail, Muhammad; Nazeeruddin, Mohammad Khaja
Abstract : Metal‐halide perovskites are optoelectronic materials applied to solar cells as a light absorber due to their excellent optoelectronic properties. The power conversion efficiency of perovskite solar cells (PSCs) reaches 25.7% certified, which stands in comparison with Si solar cells. Importantly, compositional engineering of perovskites has been one of the keys to the breakthrough. However, the presence of defects within perovskites is a matter of importance as it can cause nonradiative recombination of charge carriers. In addition, defect migration can degrade the photovoltaic performance and stability of PSCs. Previous studies have commonly addressed that iodide‐related defects such as interstitial iodide and iodide vacancy are problematic due to their low formation energy. Thus, halide engineering is imperative to mitigate the defect‐related dynamics and improve the materials quality of perovskites. In this sense, superhalogen is a promising candidate for defect passivation and stabilization of perovskites based on its higher electronegativity and electron affinity than halides, which are beneficial to the formation of a more robust interaction with adjacent elements in perovskites. This perspective gives an overview of studies regarding the use of superhalogen to develop efficient and stable PSCs and concludes with an outlook of further research directions. Abstract : Superhalogen is a promising candidate for defect passivation and stabilization of metal‐halide perovskites due to its higher electronegativity and electron affinity than halides. This perspective gives an overview of studies regarding the use of superhalogen to develop efficient and stable perovskite solar cells and concludes with an outlook of further research directions.